Degradation of norfloxacin by thermally activated persulfate: kinetics, optimization and pathways - Fanghua Zhao; Shanjun Liu; Jingwei Geng; Ran Wei; Yuanjing Wen; Shan Sun (Discover Chemistry)
Abstract Norfloxacin was degraded by thermally activated persulfate, and its degradation kinetics, influence factors and reaction pathways were investigated. The degradation rate of norfloxacin could reach 97.7% within 120 min under optimal conditions. The degradation reaction followed pseudo-first-order kinetics with an activation energy of 83.4 kJ/mol. Norfloxacin in cation form was beneficial to its degradation, and a low concentration of chloride ions had little effect on the norfloxacin degradation while PO4 3− could significantly inhibit the norfloxacin degradation. Eight intermediate products were identified, which inferred that the initiating reaction of the norfloxacin degradation by thermally activated persulfate mainly occurred on the piperazine ring. These findings provide critical insights for implementing the advanced oxidation processes based on thermally activated persulfate in antibiotic wastewater remediation.